2021
DOI: 10.1007/s10433-021-00625-7
|View full text |Cite
|
Sign up to set email alerts
|

Older Chinese migrants in coronavirus pandemic: exploring risk and protective factors to increased loneliness

Abstract: Older migrants may be one of the most vulnerable populations during the coronavirus pandemic, yet the degree of impact remains largely unknown. This study explores (1) the consequences of the coronavirus pandemic for older Chinese migrants in Belgium and the Netherlands in terms of increased loneliness and its risk factors (reduced in-person contact, decreased social participation, feelings of existential threat) and protective factors (increased non-in-person contact, more individual activities), and (2) whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Second, the main findings of this scoping review show that although researchers and practitioners raised concerns about the experience and potential adverse health outcomes of social isolation and loneliness resulting from physical/social distancing (Campbell, 2020;Lee and Miller, 2020), the limited available empirical evidence does not fully support these concerns. In the study by Pan et al (2021), older immigrants reduced their in-person contacts but augmented their contacts with family and friends through telephone or social media, a finding consistent with that reported by Ro ¨hr et al (2020). This switch in the means of contact, along with living arrangement (where older immigrants tend to live with their children and grandchildren), may have contained older immigrants' experiences and feelings of isolation and loneliness.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Second, the main findings of this scoping review show that although researchers and practitioners raised concerns about the experience and potential adverse health outcomes of social isolation and loneliness resulting from physical/social distancing (Campbell, 2020;Lee and Miller, 2020), the limited available empirical evidence does not fully support these concerns. In the study by Pan et al (2021), older immigrants reduced their in-person contacts but augmented their contacts with family and friends through telephone or social media, a finding consistent with that reported by Ro ¨hr et al (2020). This switch in the means of contact, along with living arrangement (where older immigrants tend to live with their children and grandchildren), may have contained older immigrants' experiences and feelings of isolation and loneliness.…”
Section: Discussionsupporting
confidence: 87%
“…This switch in the means of contact, along with living arrangement (where older immigrants tend to live with their children and grandchildren), may have contained older immigrants' experiences and feelings of isolation and loneliness. Pan et al (2021) found that most older immigrants reported no change in their level of loneliness during, as compared to pre-pandemic. This finding is comparable to those reported in other studies targeting the general older adult population in the USA (Rorai and Perry, 2020), the UK (Creese et al, 2021) and Germany (Ro ¨hr et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations